GENERASI ALPHA : TINGGAL DIANTARA - Raymond Arnold Manuel; Agustinus Sutanto (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The current Alpha generation is the youngest generation born in 2011 with an increasingly advanced technological approach, its familiarity with the world of technology is inseparable, but the Alpha generation classification does not materialize because there is no equitable distribution of education, facilities, and systems that are left behind. The urban village community experiences gaps so that some have to adapt to their abilities. This study uses an experimental material method using nails and magnets to create a unique spatial space. The resulting reaction becomes a metaphor for the movement of the Kampung Kota community in Jakarta which interacts with each other as a value for information exchange and the closeness that occurs. This is the basic concept of the experiment that has succeeded in making organic spaces for urban villagers, especially the Alpha generation who have adapted to the times.The experience that the author shares is a thought of planning for the future as an answer to "The future of living based on today". Typology of buildings designed and using material for design becomes learning material for future Living Architecture. Where technological advances create new problems about the disorder behind the modern city.  Keywords:  Alpha; Experiment; Urban Village AbstrakGenerasi Alpha saat ini merupakan generasi termuda lahir di tahun 2011 dengan pendekatan teknologi yang sudah semakin maju, kebiasaanya yang lekat dengan dunia teknologi sudah tidak bisa dipisahkan, namun klasifikasi generasi Alpha tidak terwujud karena tidak adanya pemerataan pendidikan, fasilitas, serta sistem yang tertinggal. Masyarakat kampung kota mengalami kesenjangan sehingga sebagian harus beradaptasi dengan kemampuannya. Penelitian ini menggunakan metode experiment material menggunakan paku dan magnet sehingga membuat spatial ruang yang unik. Reaksi yang dihasilkan menjadi metafor pergerakan masyarakat Kampung Kota di Jakarta yang saling berinteraksi sebagai nilai tukar informasi serta kedekatan yang terjadi. Hal ini sebagai konsep dasar experiment yang berhasil membuat ruang organik untuk masyarakat kampung kota khususnya generasi Alpha yang telah beradaptasi dengan perkembangan jaman. Pengalaman yang penulis bagikan merupakan sebuah pemikiran perencanaan dimasa mendatang sebagai jawaban dari “Masa depan berhuni berbasis hari ini”. Tipologi bangunan yang dirancang dan penggunaan material terhadap perancangan menjadi bahan pembelajaran terhadap Arsitektur Berhuni dimasa depan. Dimana kemajuan teknologi menimbulkan masalah baru tentang disorder (kekacauan) dibalik kota modern.